LOVE THE ONE YOU’RE WITH: WOMAN AT THE CROSSROADS OF TRUE LOVE AND REAL LIFE - Tatik Muflihah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
Conflict is a situation frequently occurs in people’s lives. The source of conflict is usually originated from a personal and interpersonal misunderstanding in a relationship and poor communication. As a part of human’s creativity, literary work sometimes reflects people problematic life. One of those is internal and external conflict faced by the main character of the novel Love the One You’re With by Emily Giffin. This paper aims at investigating the conflicts faced by the main character of the novel and the strategy used to resolve those. The result of the study shows that the main character of the novel faced both internal and external conflicts. The internal is the conflict of Ellen and her own mind when she run into her true love and her real life as a wife. It becomes a conflict as she trapped and started to hesitate her own self whether go along with her emotional love or go back to her husband. The external conflicts occur between Ellen and all the characters of the novel. Thus, the main character of the novel had a complicated struggle to save her marriage live.